Analisis Kualitas Perairan untuk Budidaya Ikan Air Tawar di Bendungan Batu Bulan - Yuni Intan Lestari; Dwi Mardhia; Dedi Syafikri; Neri Kautsari; Yudi Ahdiansyah (Indonesian Journal of Applied Science and Technology, 2020)
This study aims to analyze the water parameters that support fresh fish cultivation in the Batu Bulan dam, Maman Village, Moyo Hulu District. The study used a survey method at three observation locations, inlet, center, and outlet of the dam on water quality, including temperature, brightness, substrate, pH, dissolved oxygen (DO), turbidity, salinity, ammonia, Phosphate, and depth. The results showed that the inlet temperature ranges from 29,32oC, in the middle ranges from 29,91oC, and the outlet is 29.11oC. The average brightness at the inlet is 41.04 cm, the middle is 48.20 cm, and the outlet is 34.16 cm. The substrate at the inlet and in the middle is muddy while the outlet is sandy. The pH average in inlet is 6,33, in the middle is 6,58, and outlet 6,53.  Dissolved oxygen (DO) in the inlet range is 5.34 mg/l, in the middle is 5.51 mg/l, and in an outlet, it is 5.85 mg/l. Turbidity in the inlet range is 2,44 NTU, in the middle 2,67 NTU, and an outlet is 3,26 NTU. Salinity in all locations is 0 ppt. Ammonia in the inlet range is 1,01 mg/l, in the middle 0,69 mg/l and outlet is 1,1 mg/l. The average Phosphate at the inlet is one mg/l, in the middle and outlet is 0 mg/l. The status of the water eligibility for aquaculture is that the inlet and middle of the dam are suitable for cultivation, while those at the outlet are less feasible.